Strategy to Arrange Gender Responsive Budget in ex Besuki Residency - Sulistio Adiwinarto; Baktiawan Nusanto (Rechtsidee, 2015)
This study aims to determine the participation of women in development planning meeting, knowing the form of gender responsive policies, identifying the cause of the gender responsive policy problem, and strategy formulation of the budget in ex Besuki Residency such as Jember, Bondowoso, Situbondo, and Banyuwangi which still not responsive to the needs of women. In the first year, this study intends to identify the process of formulation, implementation, and evaluation of the local budget in Ex Besuki residency conducted by the respective local governments. Based on the research in the first year, researchers will formulate development strategies in the formulation of gender-responsive policies. The method of research is quantitative descriptive study, study documentation, primary and secondary data analysis, interviews and focus group discussions. In the second year of the study are expected to form a strategy and policy formulation concept of gender responsive budgeting through a combination previously existing concepts, adapted to the results of the first year of study at the study site. How To Cite: Adiwinarto, S., & Nusanto, B. (2015). Strategy to Arrange Gender Responsive Budget in ex Besuki Residency. Rechtsidee, 2(1), 65-78. doi:http://dx.doi.org/10.21070/jihr.v2i1.5